Density of f-ideals and f-ideals in mixed small degrees - H`a, Huy T`ai; Keiper, Graham; Mahmood, Hasan; O’Rourke, Jonathan L. (MATHEMATICA SCANDINAVICA, 2022)
A squarefree monomial ideal is called an f-ideal if its Stanley–Reisner and facet simplicial complexes have the same f-vector. We show that f-ideals generated in a fixed degree have asymptotic density zero when the number of variables goes to infinity. We also provide novel algorithms to construct f-ideals generated in small degrees.